Speculation for quantifying increased C4 plants under future climate conditions: Inner Mongolia, China case study. (10th August 2021) - Ma, Xueyun; Wei, Zhifu; Wang, Yongli; Wang, Gen; Zhang, Ting; Ma, He; He, Wei; Yu, Xiaoli; Li, Shangkun; Fan, Qiaohui
Abstract: Alternating conditions from cold to warm periods since the Late Glacial provided a significant contrast for future hydroclimatic variation, as did the corresponding variation in vegetation. To predict the potential variability in C3 /C4 biomass under future warmer climatic conditions, we determined the current spatiotemporal distribution of C3 and C4 vegetation by estimating the variability of δ 13 Corg values in 125 topsoil samples and investigating the geological period variability of C4 plants growing in Inner Mongolia, China. We examined the factors contributing to the growth of C4 plants and the variability in C4 plants for each 1 °C increase in temperature during recent and geological times. The results revealed that the relative abundance of C4 plants in Inner Mongolia shows an increasing trend from the northwest to the southeast. The biomass of C4 plants was found to be positively correlated with temperature, although weakly correlated with precipitation, thereby indicating that temperature is the primary climatic factor determining the growth of C4 plants in this region. Furthermore, we found that in response to each 1 °C increase in temperature, there would be an approximate 2.1% increase in the spatiotemporal variation of present-day C4 plant biomass in Inner Mongolia, whereas during the geological period, there was a corresponding increase of 10.7%. Comparatively, the spatiotemporal variation in present-day C4 biomass on the Chinese Loess Plateau has undergone a 4.0% increase in response to each 1 °C increase in temperature, whereas 6.0% and 7.5% increases in the geological period were estimated based on core samples taken from the Lantian and Xingyang sections, respectively. Interestingly, for each 1 °C increase in temperature during the current growth month of C4 plants, there is a 6.6% increase in C4 biomass, which is essentially consistent with the results obtained for the geological period results (i.e., 6.0% and 7.5% for the Lantian and Xingyang sections, respectively). The findings of this study reveal a distinct contrast in the variation of C4 plants during recent and geological periods, thereby enabling us to quantitatively estimate the potential changes in C4 vegetation in response to projected climate conditions.